Pengaruh Financial Knowledge dan Locus of Control Terhadap Perilaku Pengelolaan Keuangan Mahasiswa (Studi Kasus Mahasiswa di Surabaya) - Ramadini, Siti Hawa Tanzania; Apriyandhini, Nandira (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The current digital era has changed many things including the way people shop by offering easy access and various attractive promotions. This can encourage consumer behavior, such as the tendency to buy more goods because of discounts, flash sales, and ease of transactions. Therefore, financial management is an important thing to do for everyone, including students. This study aims to explore the influence of financial knowledge and locus of control on the financial management behavior of students in Surabaya. By having good financial knowledge, it can prevent everyone from doing wasteful or consumptive behavior. Of course, this needs to be supported by having a locus of control. Locus of control reflects an individual's belief in their ability to control the actions taken, divided into internal and external locus of control. In the context of financial management, students with an internal locus of control tend to be more proactive and responsible in managing their finances compared to those with an external locus of control. This study involved 86 student respondents with different study programs and from various universities in Surabaya. Data were collected through a questionnaire to test financial knowledge, locus of control and financial management practices. Data analysis was conducted using multiple linear regression method to identify significant relationship between financial knowledge and locus of control on financial management behavior.